2014
DOI: 10.5897/jmpr2013.5503
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi increase gallic acid production in leaves of field grown Libidibia ferrea (Mart. ex Tul.) L. P. Queiroz

Abstract: Because arbuscular mycorrhizal fungi (AMF) has been shown to induce concentration increases of pharmaceutically useful phytochemicals in some Brazilian semi-arid native plants, the current study examined whether mycorrhizal inoculation increased the production of bioactive compounds, especially gallic acid, in field grown Libidibia ferrea (Mart. ex Tul.) L. P. Queiroz plants. Seedlings were inoculated with Claroideoglomus etunicatum (W.N. Becker & Gerd.) C. Walker & A. Schüßler, Acaulospora longula Spain & N. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
3
5
2
Order By: Relevance
“…In accordance with the results by Silva et al [27], who studied the concentration of phenols in leaves of L. ferrea , seven months after the transplanting, the concentration of phenols in the bark of the stem did not differ among the treatments (Table 2 ). In contrast, Riter Netto et al [19] developed a study using screens and reported an increase in the foliar content of total phenols in Passiflora alata Curtis inoculated with C. etunicatum , Rhizophagus intraradices , and mixed inoculum ( Rhizophagus clarus and Gigaspora margarita ) in relation to the non-inoculated control.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In accordance with the results by Silva et al [27], who studied the concentration of phenols in leaves of L. ferrea , seven months after the transplanting, the concentration of phenols in the bark of the stem did not differ among the treatments (Table 2 ). In contrast, Riter Netto et al [19] developed a study using screens and reported an increase in the foliar content of total phenols in Passiflora alata Curtis inoculated with C. etunicatum , Rhizophagus intraradices , and mixed inoculum ( Rhizophagus clarus and Gigaspora margarita ) in relation to the non-inoculated control.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were recorded in inoculated C. forskohlii in field conditions with the density of the spores in the mycorrhized plants presenting differences in relation to the plants in the control treatment without inoculation and containing vermicompost [25]. Silva et al [27] recorded results that differ from our study considering that the density of the spores in the rhizosphere of L. ferrea, in field conditions, did not differ among the inoculation treatments. The higher production of these propagules in the soil guarantees new colonization sites in the L. ferrea since favorable conditions may cause the spores to germinate and colonize the host [40].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations